A high affinity kidney targeting by chitobionic acid-conjugated polysorbitol gene transporter alleviates unilateral ureteral obstruction in rats. (September 2016) - Islam, Mohammad Ariful; Kim, Sanghwa; Firdous, Jannatul; Lee, Ah-Young; Hong, Seong-Ho; Seo, Min Kyeong; Park, Tae-Eun; Yun, Cheol-Heui; Choi, Yun-Jaie; Chae, Chanhee; Cho, Chong-Su; Cho, Myung-Haing
Abstract: Aside from kidney transplantation – a procedure which is exceedingly dependent on donor-match and availability leading to excessive costs – there are currently no permanent treatments available which reverse kidney injury and failure. However, kidney-specific targeted gene therapy has outstanding potential to treat kidney-related dysfunction. Herein we report a novel kidney-specific targeted gene delivery system developed through the conjugation of chitobionic acid (CBA) to a polysorbitol gene transporter (PSGT) synthesized from sorbitol diacrylate and low molecular weight polyethylenimine (PEI) carrying hepatocyte growth factor (HGF) gene to alleviate unilateral ureteral obstruction (UUO) in rats. CBA-PSGT performed exceptionally well for targeted delivery of HGF to kidney tissues compared to its non-targeted counterparts ( P  < 0.001) after systemic tail-vein injection and significantly reduced the UUO symptoms, returning the UUO rats to a normal health status. The kidney-targeted CBA-PSGT-delivered HGF also strikingly reduced various pathologic and molecular markers in vivo such as the level of collagens (type I and II), blood urea nitrogen (BUN), creatinine, and the expressions of ICAM-1, TIMP-1 and α-SMA which play a critical role in obstructive kidney functions. Therefore, CBA-PSGT should be further investigated because of its potential to alleviate UUO and kidney-related diseases using high affinity kidney targeting.